The Spiral of Silence on Political Movement of Thai Youth Under the Imagined Community from Milk Tea Alliance Tactics on Twitter - Anthika Manowong (Journal of Social Science)
The main focus of this research is how the youth demonstration started in Thailand in late 2020. It is now and this demonstration is still going on in a more severe stage as Thailand just had an election on May 14th, 2023 but the authoritarian regime seems not to respect the majority votes. The analysis since late 2020, the demonstration of Thai youths, will be discussed in this research and the main question is what is the motivation of Youth’s demonstration will be analyzed. Why are high school and elementary school students walking out on the street for a political movement, and some out mobilizing in front of the Ministry of Education to represent people's opinions on political changes? When comparing student activism in Thailand on the Day of Great Sorrow "Wan Maha Wippayok" in 1973 and 1976, one sees that the two movements were to promote anti-dictatorship in Thailand. The people who played the role of a striker were university students. In contrast, the demonstration in 2020, it differs from the demonstrations in the 1970s; in the 2020 demonstration, people from all levels participated in this protest, especially elementary school and high school students. This research discovered the deep roots of this protest and how the government and Thai Youth should encounter it halfway through this shift so that the movement will achieve its goal and have less harm on the current economy. An aggressive movement has no benefit to Thai people and the economy. It destroys national GDP and wastes too much time rebuilding the economy under an aging society. Anonymously interviewing the scholars and students who joined the demonstration, data analysis, and online survey from the people who attended Thai schools are the key to finding an answer to the research questions.